2012
DOI: 10.1371/journal.pone.0038601
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Spread of Bos taurus: New Clues from Mitochondrial Genomes Belonging to Haplogroup T1

Abstract: BackgroundMost genetic studies on modern cattle have established a common origin for all taurine breeds in the Near East, during the Neolithic transition about 10 thousand years (ka) ago. Yet, the possibility of independent and/or secondary domestication events is still debated and is fostered by the finding of rare mitochondrial DNA (mtDNA) haplogroups like P, Q and R. Haplogroup T1, because of its geographic distribution, has been the subject of several investigations pointing to a possible independent domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 26 publications
5
111
1
Order By: Relevance
“…In Africa, haplotypes from haplogroups other than T1 have been found only in Egypt (combined frequency 38.5%) and Northwest Africa (less than 2%) and are completely absent in the rest of the continent. A recent comprehensive study of whole mtDNA of the T1 haplogroup identified eight haplotypes as founders of the African T1 population [11]. Estimates of coalescence times for the T1 sub-haplogroups (6,200 to 12,900 BP) and their current geographic distributions are compatible with a Southwest-Asian origin for most T1 sub-haplogroups, which for sub-haplogroup T1c1 has been confirmed by it discovery in Iraq [14].…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In Africa, haplotypes from haplogroups other than T1 have been found only in Egypt (combined frequency 38.5%) and Northwest Africa (less than 2%) and are completely absent in the rest of the continent. A recent comprehensive study of whole mtDNA of the T1 haplogroup identified eight haplotypes as founders of the African T1 population [11]. Estimates of coalescence times for the T1 sub-haplogroups (6,200 to 12,900 BP) and their current geographic distributions are compatible with a Southwest-Asian origin for most T1 sub-haplogroups, which for sub-haplogroup T1c1 has been confirmed by it discovery in Iraq [14].…”
Section: Resultsmentioning
confidence: 82%
“…As shown for haplogroup T1 in Africa [11,44], whole-mtDNA sequencing may detect additional sub-haplogroups informative for movements of cattle between or within continents and expansion of populations. Ancient DNA studies contribute essentially to the historic reconstructions by providing geographic and historic anchor points for specific haplotypes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent evidence, both in livestock and wildlife, showed that molecular phylogenies based on a short and fastevolving portion of mtDNA, such as the control region, can be heavily affected by the effects of NUMTs (NUclear Mitochondrial Transpositions, also called pseudogenes; Hassanin et al, 2010;Moyle et al, 2013) and homoplasy (McCracken and Sorenson, 2005;Bonfiglio et al, 2012), which may mask the actual extent of divergence/similarity between mitochondrial lineages. mtDNA control region analysis in cattle proved to be inadequate for a thorough characterization of maternal lineages, and a far more precise picture has been obtained from complete sequences of mitochondrial genomes (Achilli et al, 2008;Bonfiglio et al, 2010Bonfiglio et al, , 2012.…”
Section: Reconstruction Of Goat Evolutionary Historymentioning
confidence: 99%
“…mtDNA control region analysis in cattle proved to be inadequate for a thorough characterization of maternal lineages, and a far more precise picture has been obtained from complete sequences of mitochondrial genomes (Achilli et al, 2008;Bonfiglio et al, 2010Bonfiglio et al, , 2012. Next generation sequencing technologies now permit the high throughput/low cost analysis of entire mitochondrial genomes at the maximum resolution, and have become the common standard for the investigation of the human maternal lineages.…”
Section: Reconstruction Of Goat Evolutionary Historymentioning
confidence: 99%